Analysis of the Correlation between Cross-Border E-Commerce and Economic Growth Based on Hierarchical Multilevel Gray Evaluation Model - Nie Chen (Journal of Mathematics)
Cross-border e-commerce is a new form of global trade development under the background of “Internet+,” and it is also a new engine driving economic development. Cross-border e-commerce is growing rapidly and has broad development prospects. As a pioneering pilot zone for comprehensive cross-border e-commerce, it has played a leading role in the development of the country’s cross-border e-commerce industry. This paper takes China’s 35 cross-border e-commerce comprehensive pilot areas as the research object, selects the annual data of 31 provinces across the country, and conducts an empirical research based on the gray-related Internet development level and economic growth. It analyzes the influencing factors of cross-border e-commerce development, constructs a cross-border e-commerce development influencing factor model, and applies gray theory to conduct an empirical analysis of the correlation between cross-border e-commerce development influencing factors and cross-border e-commerce. The research results show that foreign direct investment has the greatest correlation with the number of websites and webpages; the number of patent applications has the greatest correlation with the number of domains and websites; the total fixed assets have the greatest correlation with the number of Internet users and the number of mobile phones at the end of the year; the total amount of foreign investment enterprises in and out. It has the greatest correlation with the number of URLs and Webpages; GDP has the greatest correlation with the number of Internet users and the number of mobile phones at the end of the year. The Internet infrastructure and popularity have a close relationship with economic growth, and the relationship between foreign investment and patent applications and the level of Internet development is more significant.